Eu3+-tetrakis β-diketonate complexes for solid-state lighting application - Leite Silva, Camila M.B. [UNESP]; Bispo-Jr, Airton G. [UNESP]; Canisares, Felipe S.M. [UNESP]; Castilho, Shirley A. [UNESP]; Lima, Sergio A.M. [UNESP]; Pires, Ana M. [UNESP] (Wiley, 2019)
Eu3+–β-diketonate complexes are used, for example, in solid-state lighting (SSL) or light-converting molecular devices. However, their low emission quantum efficiency due to water molecules coordinated to Eu3+ and low photostability are still problems to be addressed. To overcome such challenges, we synthesized Eu3+ tetrakis complexes based on [Q][Eu(tfaa)4] and [Q][Eu(dbm)4] (Q1 = C26H56N+, Q2 = C19H42N+, and Q3 = C17H38N+), replacing the water molecules in the tris stoichiometry. The tetrakis β-diketonates showed desirable thermal stability for SSL and, under excitation at 390 nm, they displayed the characteristic Eu3+ emission in the red spectral region. The quantum efficiencies of the dbm complexes achieved values as high as 51%, while the tfaa complexes exhibited lower quantum efficiencies (28–33%), but which were superior to those reported for the tris complexes. The structures were evaluated using the Sparkle/PM7 model and comparing the theoretical and the experimental Judd–Ofelt parameters. [Q1][Eu(dbm)4] was used to coat a near-UV light-emitting diode (LED), producing a red-emitting LED prototype that featured the characteristic emission spectrum of [Q1][Eu(dbm)4]. The emission intensity of this prototype decreased only 7% after 30 h, confirming its high photostability, which is a notable result considering Eu3+ complexes, making it a potential candidate for SSL.
Keywords: dbm; energy transfer; light-emitting diodes; Sparkle/PM7 model; tfaa